Views of Genetics Health Professionals on the Return of Genomic Results. Issue 4 (2nd June 2013) - Grove, Megan E.; Wolpert, Maya N.; Cho, Mildred K.; Lee, Sandra Soo‐Jin; Ormond, Kelly E.
Abstract: As exome and whole genome sequencing become clinically available, the potential to receive a large number of clinically relevant but incidental results is a significant challenge in the provision of genomic counseling. We conducted three focus groups of a total of 35 individuals who were members of ASHG and/or NSGC, assessing views towards the return of genomic results. Participants stressed that patient autonomy was primary. There was consensus that a mechanism to return results to the healthcare provider, rather than patient, and to streamline integration into the electronic health record would ensure these results had the maximal impact on patient management. All three focus groups agreed that pharmacogenomic results were reasonable to return and that they were not felt to be stigmatizing. With regard to the return of medically relevant results, there was much debate. Participants had difficulty in consistently assigning specific diseases to 'bins' that were considered obligatory versus optional for disclosure. Consensus was reached regarding the importance of informed consent and pretest counseling visits to clarify what the return of results process would entail. Evidence based professional guidelines should continue to be developed and regularly revised to assist in consistently and appropriately providing genomic results to patients.